2010
DOI: 10.1097/pec.0b013e3181ef04a3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Occult Pneumonia in a Pediatric Emergency Department

Abstract: Occult pneumonia was identified in 1 of 15 patients undergoing CXR without respiratory distress or ausculatory findings. Obtaining a CXR for the detection of OP in children without cough and with fever for less than 1 day in duration should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This number is almost in line with the results of the present study (6). In the study by Shah et al to determine the predictive factors and incidence of latent pneumonia in patients who had undergone chest x-ray examination; out of 308 studied patients, 21 (6.8%) had latent pneumonia, which is almost in accordance with the results of present study (9). In the study by Bachur et al, 225 patients received chest x-ray examination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This number is almost in line with the results of the present study (6). In the study by Shah et al to determine the predictive factors and incidence of latent pneumonia in patients who had undergone chest x-ray examination; out of 308 studied patients, 21 (6.8%) had latent pneumonia, which is almost in accordance with the results of present study (9). In the study by Bachur et al, 225 patients received chest x-ray examination.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the mean WBC count in the bacterial pneumonia, viral infection, and other disease groups was reported 13.79×10³ ± 3.98×10³, 10.82×10³ ± 4.47×10³, and 11.97×10³ ±4.92×10³, respectively, showing no significant difference (P = 0.511). In the study by Shah et al, the mean WBC count in the latent pneumonia and non-pneumonia groups was reported 15.40×10³ and 17.60×10³, indicating no significant difference (P = 0.74) (9). In the research by Rutman et al, the mean WBC count in the pneumonia and non-pneumonia groups was 26.30×10³ and 24.10×10³, respectively (10), showing no significant difference, and being in line with the results of present study.…”
Section: Discussionmentioning
confidence: 90%
“…However, the challenge lies not only in identifying children with, for example, pneumonia among children with signs of a lower respiratory tract infection but rather in designating risk thresholds to all children with fever. Indeed, it has been shown that the incidence of radiographically proved pneumonia among children with fever without a clear focus is significant (5-9%),48 49 50 51 and was especially high in children with raised laboratory markers (13-18%) 4851 Besides, not only did our prediction model verify known predictors of pneumonia in children at increased risk of a lower respiratory tract infection, supporting the validity of our results,4 38 52 but perhaps more importantly it also simultaneously showed that the presence of these signs and symptoms was valuable for ruling out other SBIs.…”
Section: Discussionmentioning
confidence: 99%
“…We defined Pneumonia as a Chest X-Ray reported by a radiologist as definite or probable for a pneumonia ("Infiltrate", "consolidation" or "concerning for developing pneumonia") irrespective of microbiological results as these are low yield [19]. This definition reflects clinical practice.…”
Section: Definitionsmentioning
confidence: 99%